Avaliação do plano de manejo de camarões peneideos na plataforma continental de sergipe, brasil - Santos, Rafael de Carvalho; da Silva, Sonja Luana Rezende; da Costa, Rogério Caetano [UNESP]; Davanso, Thiago Maia [UNESP]; Hirose, Gustavo Luis (Boletim do Instituto de Pesca, 2017)
This study evaluated if the temporal and spatial reproduction and recruitment of the main species of marine shrimps exploited in the state of Sergipe (Xiphopenaeus kroyeri, Farfantepenaeus subtilis, and Litopenaeus schmitti) are being protected, in relation to the closed season based on the normative instruction MMA n° 14, of October 14th 2004. The samples were collected monthly from September 2013 to August 2014 at the continental shelf of Sergipe, in nine transects, distributed in the depths of 5, 15, and 30 m using a shrimping boat equipped with double ring nets. After sampling, we identified shrimps to the species level; subsampled, sexed them, measured carapace length, and observed the gonads. Recruitment and reproduction in the three species occur continuously, albeit with intensity peaks. Regarding space, reproductive individuals and recruits were more abundant at 30 m in the case of F. subtilis, while for X. kroyeri and L. schmitti, higher abundances were found at 5 and 15 m. The current normative instruction partially protects the reproductive and juveniles categories of these species, mainly F. subtilis. Thus, we suggest closed seasons at breeding and recruitment seasons of F. subtilis, since the area set by IBAMA already protects other species throughout the year.
Evaluation of the management plan for penaeid shrimps in the continental shelf of sergipe, Brazil
Keywords: Farfantepenaeus; Fishery; Litopenaeus; Recruitment; Reproductive period; Xiphopenaeus